Designing Scalable Technology Architectures for Customer Data in Group Insurance and Investment Platforms (International Journal of Scientific Research and Management (IJSRM), 2020)
Designing scalable architecture frameworks for customer data have become increasingly important. While technology transcends most industry barriers, the cross-border, multi-national nature of the Group Insurance and Investment services operational delivery models create heightened requirements for assessing and building those capabilities. As these organizations with international footprint continue to evolve their digital strategies, key pillars of their technology architecture must mature both from an operations and governance structure perspective for continued success. Designing customer data architecture and structure, especially around the Canadian market, has become even more challenging in the current and post world. This is compounded by the fact that while the accessing and servicing of client customer data is generally addressable via digital fabric capabilities, the transferring and modifying of sensitive customer data must follow established routine and tested procedures. Regulatory control and governance of that architecture is fundamental for a tier-1 life and health insurer’s long-term brand health and reputation. The analysis of the investment portfolios that reflect these digital strategies and customer data architecture designs must encompass a levers framework that contemplates IT investments and growth as enterprise capability sources. Examining the investment and profitability issues through the lenses of portfolio theory, we have described ten functional pillars foundational to technology architecture in the digital age. Embedded within these pillars is a set of practical considerations, reflective of the lessons learned the hard way, that insurance organizations can replicate for their benefit. We use a life and health insurer and its business for the purposes of demonstration of diagnostic building blocks and the capabilities roadmap in delivering on a group insurance and investment customer-centric technology architecture.